Ayurvedic Dosha Detection and Corrective Measures through Labview - Madan, Aakanksha (My University, 2015)
Prevention is always better than cure. A proper ayurvedic diet itself can be used to balance tridosha and prevents occurrence of any disease beforehand. This work is an ayurveda based healthcare management system. This system embodies the traditional expertise of ayurveda acharyas into a scientific form with the help of LabVIEW. It can be used by anyone without any pre-qualification. It works on questions related to various features of the body which can be judged by individual itself as per his/ her own observation. This method is highly apt as no one can judge anyone better than their own self. Therefore approximately 320 questions have been selected to identify a person’s prakriti. All daily used food items have been researched upon well in order to design diet according to the subject so as to rectify the imbalance of dosha specific to that subject. This highly precise LabVIEW application balances the dosha and manages the daily calorie intake in accordance with the persisting season through 84 different ayurvedic diets. This system is user friendly, very accurate and has low latency time
ME-EIC-Thesis
Keywords: DOSHA; VATA; PITTA; KAPHA; Diet Chart; Electrical and Instrumentation; EIC